Experimental Study to Improves Covid-19 Health Protocol Compliance with High Threat and High Efficacy Poster - Eric Fernardo (Jurnal Komunikasi, 2021)
This study examines the health campaign of Covid-19 using the extended parallel process model (EPPM) theory. The objective and gap that was successfully filled by this research are to examine the effect of the poster with high threat and high efficacy to obedience to implement Covid-19 health protocol in Indonesia context. In contrast, obedience is divided into aspects of attitude and second aspects of behaviour according to Blass's concept of obedience. This study uses a quantitative approach with an experimental method by grouping respondents into two groups. The first is the treatment group that received a poster. The second is a control group that did not receive any posters. The total number of respondents of this research was 95, representing proportionally by categories of sex and categories of age. This research has met the scientific principles required. This study found that poster with high threat and high efficacy has a significant effect of improving the attitude aspects of obedience to implement Covid-19 health protocol because when respondents saw a poster with high threat and high efficacy, respondents felt that the threat posed by covid-19 was so high that could turn into death, another reason is a poster with high threat, and high efficacy evokes the memory of respondents to remember their relatives, close person or family who have been confirmed positive with Covid-19 virus. This study also found that poster with high threat and high efficacy does not affect behavioural aspects. This means that posters with high threat and high efficacy proved to make changes with the attitude aspects to improve people obedience to implement Covid-19 health protocol but, it has not been proven to change the behavioural aspects.Riset ini meneliti kampanye kesehatan Covid-19 menggunakan pisau analisa teori extended parallel process model (EPPM). Tujuan dan celah yang berhasil diisi dari penelitian ini dibandingkan penelitian terdahulu adalah menguji pengaruh pemberian poster ancaman tinggi dan efikasi tinggi terhadap kepatuhan protokol kesehatan Covid-19 dalam konteks Indonesia, adapun kepatuhan dibagi ke dalam dua aspek yakni aspek sikap dan aspek perilaku sesuai konsep kepatuhan Blass. Penelitian ini menggunakan pendekatan kuantitatif yakni metode eksperimen dengan membagi responden ke dalam dua kelompok yang pertama adalah kelompok perlakuan/treatment yang mendapat poster dan kedua adalah kelompok kontrol yang tidak mendapat poster, jumlah responden sebanyak 95 yang mewakili masing-masing kategori jenis kelamin dan kategori usia secara proporsional. Riset ini telah dilaksanakan mengacu pada kaidah-kaidah ilmiah. Hasil penelitian menemukan bahwa pemberian poster ancaman tinggi dan efikasi tinggi berpengaruh signifikan meningkatkan aspek sikap kepatuhan protokol kesehatan Covid-19 karena saat melihat poster ancaman tinggi dan efikasi tinggi responden merasa ancaman yang ditimbulkan oleh Covid-19 amat besar hingga dapat menimbulkan kematian, alasan lain yakni poster ancaman tinggi dan efikasi tinggi membangkitkan memori responden yang teringat orang dekat, kerabat maupun keluarga yang pernah terkonfirmasi positif virus Covid-19. Penelitian ini juga menemukan bahwa poster ancaman tinggi dan efikasi tinggi tidak berpengaruh terhadap aspek perilaku. Artinya pemberian poster ancaman tinggi dan efikasi tinggi terbukti mengubah aspek sikap untuk lebih mematuhi protokol kesehatan Covid-19 tetapi, tidak terbukti mengubah aspek perilaku.